Action-research methodology to improve performance using lean production tools - Costa, Eric (2014)
This paper presents a five months Action-Research project developed in the context of a lean production implementation initiative in an elevators company. The project consisted in (i) analysis and diagnosis of two productive areas of the company’s production system and (ii) development and implementation of improvement proposals based on lean production tools and techniques. The sectors involved were the metal-mechanic area and the final assembly of the elevators doors. Improvement proposals were developed and implemented, based on SMED, 5S, Visual Management and Standard Work. The main results achieved were the reduction of time spent on setups, work-in-process, defects and distances travelled by operators, along with the standardization of some production processes and the improvement on the production system’s organization. The economic impact of these improvements was a gain of approximately 3,143.39 €/year for one sector and about 2,475.66 €/year for the other. These results reinforce the importance of the company’s lean initiative.